The Influence of Equipment and Environment on Children and Young Adults Learning Aquatic Skills - van Duijn, Tina; Ng, Jonathan Leo; Burnay, Carolina; Anderson, Neil; Uehara, Luiz; Cocker, Kane; Button, Chris (Frontiers in Psychology, 2021)
Learning aquatic skills is an important component of developing physical literacy in children. Aquatic skills such as floating, swimming and safe entry/exit promote engagement in different water environments and may help preserve lives in an emergency. This scoping review was conducted to evaluate the influence of task constraints (i.e., equipment) and environmental constraints (i.e., physical and social) on how children learn foundational aquatic skills. In developed countries, children are typically taught in swimming pools under direct supervision. It is also not uncommon to see children and infants learning to swim with assistive equipment (e.g., buoyancy aids). However, perhaps surprisingly, the evidence on how and where children learn aquatic skills does not uniformly promote such practices. For example, the use of flotation devices has not been proven to aid skill learning. Some researchers have advocated that children should learn aquatic skills whilst wearing outdoor clothing. One benefit of children wearing clothing is an increased capacity to practise in colder water (such as the ocean, rivers or lakes). Overall, whilst practitioners often use equipment for various reasons it seems that not all equipment is equally useful in promoting the acquisition of aquatic skills. In less developed countries, with limited access to swimming pools and fewer resources for private instruction, a range of different open water aquatic environments and practices, such as swimming in temporarily flooded areas, have been reported. Such strategies are in urgent demand of further research given that drowning rates in less developed countries around the world exceed those in developed nations. It can be argued that learning in pools does not afford the opportunities to develop the whole range of adaptive skills that may be required in different open water environments such as navigating currents and waves, floating whilst clothed, or making life-saving decisions. Consequently, a shift towards teaching in open water environments has occurred in several countries. This review provides an evidence-base upon which practitioners can design more effective aquatic education programs for children.